Preparation method for synthesizing C / Bi / Bi2WO6 heterojunction photocatalyst through rotational crystallization method and application of C / Bi / Bi2WO6 heterojunction photocatalyst

The C/Bi/Bi2WO6 heterojunction photocatalyst was synthesized by rotary crystallization. Combined with SPR effect and non-metal doping, the problems of weak absorption capacity of Bi2WO6 photocatalysts in the visible light range and low photogenerated carrier separation efficiency were solved, and the photocatalytic activity and antibiotic degradation efficiency were significantly improved.

CN119500104APending Publication Date: 2025-02-25HANJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665088.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing Bi2WO6 photocatalysts have weak absorption capacity in the visible light range and low photogenerated carrier separation efficiency, resulting in low efficiency in degrading antibiotics in water bodies.

Method used

C/Bi/Bi2WO6 heterojunction photocatalyst was synthesized by rotary crystallization method, and Bi nanospheres were deposited on the flower-like Bi2WO6 surface using the SPR effect to improve the photogenerated carrier separation efficiency and enhance the visible light response range through non-metal doping.

Benefits of technology

The photocatalytic activity of the photocatalyst was significantly improved and the degradation efficiency of antibiotics was enhanced, which was specifically manifested as the degradation rates of norfloxacin and ciprofloxacin reached 93.4% and 90.1% respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500104A_ABST
    Figure CN119500104A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application for synthesizing a C / Bi / Bi2WO6 heterojunction photocatalyst through a rotational crystallization method, Bi nanospheres are deposited on the surface of flower-shaped Bi2WO6 by utilizing an SPR effect, so that the separation efficiency of Bi2WO6 photon-generated carriers is improved, the photocatalytic reaction performance is enhanced, the rotational crystallization method is combined with the SPR effect, and the photocatalytic performance is improved. A novel composite photocatalyst C / Bi / Bi2WO6 is prepared by using a rotational crystallization method for the first time, the catalytic activity is enhanced by changing the morphology, the visible light response range is enhanced by doping nonmetal (such as C, N or S), and the photocatalytic activity is further improved. After the C / Bi / Bi2WO6 heterojunction photocatalyst is subjected to photocatalysis for 60 minutes, the degradation rate of the C / Bi / Bi2WO6 heterojunction photocatalyst on norfloxacin NOR is as high as 93.4%, and the degradation rate on ciprofloxacin CIP is as high as 90.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a field, and in particular to a preparation method and application of a C / Bi / Bi2WO6 heterojunction photocatalyst synthesized by a rotational crystallization method. Background Art

[0002] Antibiotics such as fluoroquinolones, tetracyclines, and sulfonamides are often found in wastewater in nature and are difficult to self-degrade. Antibiotics are widely used in the medical industry due to their low price, but they are difficult to be completely absorbed by nature and the human body. Unabsorbed antibiotics have the characteristics of low concentration and high toxicity, which will have an adverse impact on the natural environment after being discharged into nature. Among the many methods for degrading antibiotics, photocatalytic technology stands out as a highly anticipated method among chemical methods. Photocatalytic technology uses sunlight as energy, has the advantages of high efficiency, non-toxicity, and greenness, and has good application prospects in removing antibiotics from water bodies. Therefore, it is urgent to develop efficient and environmentally friendly photocatalysts for removing antibiotics from water bodies.

[0003] So far, people have found that bismuth-based materials such as BiOX (X = Cl, Br, I), Bi2MoO6, and Bi2SiO5 have received extensive attention in the field of photocatalysis due to their unique layered structure. Bi2WO6 has attracted much attention due to its unique crystal structure, excellent photoelectric properties, and excellent chemical stability, but it has the disadvantages of low efficiency in separating photogenerated carriers and weak absorption capacity in the visible light range. Therefore, there is an urgent need for a new catalyst that can improve the photocatalytic activity and the efficiency of degrading antibiotics in wastewater, as well as a method for preparing the same. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a preparation method and application of a C / Bi / Bi2WO6 heterojunction photocatalyst synthesized by a rotational crystallization method. In order to improve the photocatalytic performance of Bi2WO6, the present invention utilizes the SPR effect to deposit Bi nanospheres on the surface of flower-shaped Bi2WO6, so that the separation efficiency of photogenerated carriers of Bi2WO6 is improved, thereby enhancing the photocatalytic reaction performance. The rotational crystallization method is combined with the SPR effect, and a novel composite photocatalyst C / Bi / Bi2WO6 is prepared for the first time by the rotational crystallization method. The catalytic activity is enhanced by changing the morphology, and the visible light response range is enhanced by doping with non-metals (such as C, N or S), thereby further improving the photocatalytic activity, thereby solving the problems mentioned in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a C / Bi / Bi2WO6 heterojunction photocatalyst by a rotational crystallization method, comprising the following steps:

[0006] S1. Add Bi(NO3)3·5H2O to HNO3 solution and disperse by ultrasonic, then add ethylenediaminetetraacetic acid and stir vigorously to mix, adjust pH value with ammonia solution, and vacuum dry to obtain precursor EDTA-Bi;

[0007] S2, dissolving Bi(NO3)3·5H2O in ethylene glycol, then adding a certain amount of EDTA-Bi powder to the above solution and stirring to obtain solution A;

[0008] S3, dissolving Na2WO4·2H2O in ethylene glycol to obtain solution B;

[0009] S4. Mix the A and B solutions in ethanol and stir, transfer to a reactor for rotational crystallization, wash and dry the obtained solid product, and then obtain a C / Bi / Bi2WO6 heterojunction photocatalyst.

[0010] Preferably, in step S1, the ratio of Bi(NO3)3·5H2O, HNO3 and ethylenediaminetetraacetic acid is 10mmol:30mL:10mmol.

[0011] Preferably, in step S1, the concentration of the aqueous ammonia solution is 7-8 mol / L, and the pH value is 5-7; and the vacuum drying is performed at 100° C. for 20 h.

[0012] Preferably, in step S2, the ratio of Bi(NO3)3·5H2O to ethylene glycol is 7 mmol:10 mL; and the amount of EDTA-Bi powder added is 0.03-0.7 g.

[0013] Preferably, in step S3, the ratio of Na2WO4·2H2O to ethylene glycol is 3.5 mmol:10 mL.

[0014] Preferably, in step S4, the rotational crystallization speed is 60 rpm-150 rpm, the temperature is 120° C.-160° C., and the time is 24 hours.

[0015] Preferably, the mass percentage of Bi / bismuth tungstate is 1-20wt%; and the drying treatment is vacuum drying at 80°C for 12h.

[0016] On the other hand, to achieve the above-mentioned purpose, the present invention also provides the following technical scheme: an application of a C / Bi / Bi2WO6 heterojunction photocatalyst, comprising: photocatalysis for 60 minutes, wherein the C / Bi / Bi2WO6 heterojunction photocatalyst degrades norfloxacin NOR by up to 93.4% and degrades ciprofloxacin CIP by up to 90.1%.

[0017] The beneficial effects of the present invention are as follows: the present invention successfully constructs a C / Bi / Bi2WO6 composite photocatalyst with strong interface interaction by combining the rotational crystallization method and the SPR effect of introducing non-precious metals, and uses norfloxacin and ciprofloxacin as probe reactions to prove the influence of different rotation conditions on the photocatalyst. The results show that the rotational crystallization method converts mechanical kinetic energy into potential energy, accelerates the growth of the crystal nucleus, and at the same time, the rotational crystallization method can cause the intermittent movement of the crystal nucleus to produce a cavity structure. The Fermi level (E f ) difference triggers electron transfer after coupling of the three materials, thus generating an internal electric field (IEF) at the interface, providing directional acceleration for the effective separation of photogenerated charges and maintaining the excellent redox ability of the semiconductor. The resonant photons generated by the metal nanoparticles produce collective resonance, further causing the separation of photogenerated carriers and increasing the photocatalytic performance. The degradation rate of norfloxacin and ciprofloxacin in 60 minutes of photocatalysis is as high as 93.4%, and the degradation rate of ciprofloxacin is as high as 90.1%. The free radical capture experiment shows that in the process of photocatalytic degradation of antibiotics, the main active substances are holes, hydroxyl radicals and superoxide radicals. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : are XRD diagrams of the composite samples in the embodiments of the present invention, a is the XRD diagram of the composite samples with different loading amounts; b is the XRD diagram of the composite samples with the best loading amounts at different rotation speeds;

[0019] Figure 2 FT-IR images of composite samples with different loading amounts in the embodiments of the present invention;

[0020] Figure 3 The SEM images of the composite sample CBWO-5 of the embodiment of the present invention at static state and different rotation speeds: (a, d) static state; (b, e) 60 rpm; (c, f) 90 rpm;

[0021] Figure 4 This is a TEM image of the composite sample HCBWO-5 at a rotation speed of 90 rpm in an embodiment of the present invention;

[0022] Figure 5 Schematic diagram of X-ray photoelectron spectrum of the composite material of the embodiment of the present invention, a is the full XPS spectrum of HCBWO-5; b is Bi 4f, c is W4f, d is C1s;

[0023] Figure 6 BET diagrams of HCBWO-5 and CBWO-5;

[0024] Figure 7 Schematic diagram of composite materials with different proportions and dynamic and static comparison; a is the Uv-vis diagram; b is the Tauc diagram;

[0025] Figure 8 Schematic diagram of the photoelectrochemical performance of the composite material of the embodiment of the present invention; a is the impedance diagram, and b is the photocurrent response;

[0026] Fig. 9 Schematic diagram of photocatalytic degradation of composite materials according to embodiments of the present invention, (a) (c) are degradation diagrams of composite catalysts with different proportions for degradation of NOR and CIP, (b) (d) are first-order kinetic models with different proportions;

[0027] Fig.10 Schematic diagram of the NOR degradation cycle experiment of HCBWO-5 catalyst;

[0028] Fig.11 Schematic diagram of free radical capture of composite materials according to an embodiment of the present invention; a is a data diagram of CIP free radical capture, and b is a data diagram of NOR free radical capture;

[0029] Fig.12 This is a schematic diagram of the photocatalytic principle of the composite material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The reagents used in the embodiments of the present invention are: nitric acid (HNO3, 98%), ethylenediaminetetraacetic acid (EDTA, 99.5%), sodium tungstate dihydrate (Na2WO4·2H2O, 99.5%), ammonia water (NH3·H2O, 25%), bismuth nitrate pentahydrate (Bi2(NO3)3·5H2O, 99%), anhydrous ethanol (C2H6O, 99.7%), ethylene glycol (C2H6O2, 98%), ciprofloxacin (CIP, 98%), norfloxacin (NOR), disodium ethylenediaminetetraacetate (EDTA-2Na, 99%), p-benzoquinone (p-BQ, 99%), isopropyl alcohol (IPA, 99.5%), and 0.1MAgNO3 standard solution, all of which are Macklin reagents.

[0032] The present invention combines the rotational crystallization method with the SPR effect, and for the first time uses the rotational crystallization method to prepare a novel composite heterojunction photocatalyst C / Bi / Bi2WO6, and the preparation method includes the following steps:

[0033] Preparation of Precursor EDTA-Bi

[0034] 10mmol Bi(NO3)3·5H2O was added to 30mL 0.493mol / L HNO3 and ultrasonically dispersed for 30min. Subsequently, 10mmol ethylenediaminetetraacetic acid (EDTA) was added to the above solution and stirred vigorously, and the solution pH was adjusted to 6.5 with 14% ammonia water, stirred for 2h, placed in an oven at 100℃ and dried for 20h, and ground to obtain the precursor EDTA-Bi.

[0035] Preparation of composite material C / Bi / Bi2WO6

[0036] 7mmol Bi(NO3)3·5H2O was dissolved in 10mL ethylene glycol solution. Subsequently, a certain amount of precursor powder was added to the above solution and stirred for 30min; at the same time, 3.5mmol Na2WO4·2H2O was dissolved in 10mL ethylene glycol solution and added to the above solution, 40mL ethanol was added dropwise and stirred for 2h. Transferred to a 100mL reactor, kept at 160℃ for 24h at different speeds (60rpm-150rpm) and a heating rate of 5℃ / min in a homogeneous reactor, then cooled to room temperature in cold water, centrifuged and washed three times with deionized water and anhydrous ethanol, and vacuum dried at 80℃ for 12h. The Bi content was adjusted by the mass ratio of EDTA-Bi to Bi2WO6, which were 1wt%, 5wt%, 10wt% and 20wt% respectively. (hereinafter referred to as HCBWO-1, HCBWO-5, HCBWO-10 and HCBWO-20 respectively).

[0037] Photocatalytic activity test of C / Bi / Bi2WO6 composite material

[0038] The light source used in the catalytic system is a 300W xenon lamp to simulate natural light, equipped with a filter (filtering out light sources <420nm) to ensure that the entire experiment is carried out within the visible light range, and equipped with circulating condensed water to keep the entire reaction system at around 25°C. The catalytic process is as follows:

[0039] Weigh 10 mg of C / Bi / Bi2WO6 (hereinafter referred to as composite material) and add it to the photoreactor, measure 50 mL of 10 mg / L CIP solution and add it to the photoreactor to study the performance of the photocatalytic reaction, replace the CIP solution with an equal volume and concentration of NOR solution, and also conduct the performance study of the photocatalytic reaction. In order to achieve adsorption-desorption equilibrium, the mixture in the photoreactor was magnetically stirred for 30 minutes under dark conditions before turning on the light. Then a 300W xenon lamp was used to simulate natural light irradiation for photocatalytic degradation reaction. The illumination time was 60 minutes. During this period, 2 mL of the supernatant of the solution in the photoreactor was drawn with a syringe every 10 minutes. After centrifugation, the absorbance of the sample to be tested was tested at the wavelength corresponding to each antibiotic using a UV-visible spectrophotometer. (The wavelengths of CIP and NOR are both 272nm)

[0040] 50mL of 10mg / L NOR solution was measured, and 10mg of HCBWO-5 composite material was weighed and put into the photoreactor for photocatalytic reaction performance study. HCBWO-5 was replaced with the same amount of Bi2WO6, HCBWO-1, HCBWO-10 and HCBWO-20 for photocatalytic reaction performance study. The dark reaction was carried out for 30min to reach adsorption-desorption equilibrium, and then a 300W xenon lamp was used to simulate natural light for photocatalytic degradation reaction. The illumination time was 60min. During this period, 2mL of the supernatant of the solution in the photoreactor was drawn with a syringe every 10min. After centrifugation, the absorbance of the sample to be tested at a wavelength of 272nm was tested with a UV-visible spectrophotometer.

[0041] Free radical capture experiments

[0042] In the photocatalytic degradation experiment, in order to further explore the photocatalytic mechanism of C / Bi / Bi2WO6 composite materials, 5 mM disodium ethylenediaminetetraacetate (EDTA-2Na), isopropyl alcohol (IPA), p-benzoquinone (p-BQ), and 0.1 M silver nitrate standard solution (AgNO3) were added into the mixed solution as holes (h + ), hydroxyl radical (·OH - ), superoxide radicals (·O2 - ), electronic (e - ) was added. The changes in the photocatalytic activity of the catalyst-degraded NOR solution before and after the addition of the eliminator were tested and compared, and the active substances in the reaction process were explored using a UV-visible spectrophotometer at a wavelength of 272 nm. The blank control sample was the one without the addition of the eliminator. The NOR solution was replaced with a CIP solution, and the other conditions remained unchanged, and the above experiment was repeated.

[0043] Test results verification

[0044] 1. Structural characterization of photocatalysts

[0045] 1.1 XRD analysis

[0046] like Figure 1 As shown in Figure 2, the characteristic diffraction peaks with higher intensity at 28.0°, 32.9°, 47.1° and 55.9° of Bi2WO6 correspond to the (131), (002), (202) and (133) crystal planes of the orthorhombic phase of Bi2WO6 (JCPDS#39-0256), respectively. Figure 1 As shown in a, the characteristic peaks of HCBWO-X (X = 1, 5, 10, 20) and CBWO-5 are the same as those of pure Bi2WO6, and the characteristic peak of C is not observed, which may be due to its low content and uniform dispersion. Figure 1 As shown in b, the diffraction peaks of the composite material HCBWO-5 formed at different rotation speeds of 60rpm, 90rpm and 120rpm are basically the same, proving that the material is successfully composited. Since the content of Bi in EDTA-Bi is low, there is no characteristic diffraction peak of Bi in all samples, and Bi is dispersed in the material in a highly dispersed form.

[0047] 1.2 FT-IR analysis

[0048] like Figure 2 As shown, 400~1000cm -1 The main absorption band is caused by Bi-O bond, WO bond and WOW bond. -1 、573cm -1 The absorption peaks at 672 cm-1 and 672 cm-2 correspond to the deformation vibration and stretching vibration of Bi-O bonds, respectively. -1 The absorption peak at 861 cm corresponds to the stretching vibration of the WO bond. -1 、946cm -1 and 1035cm -1 The absorption peak at corresponds to the stretching vibration of the WOW bond.

[18] The characteristic diffraction peaks of the composite sample and Bi2WO6 are similar, indicating that the introduction of C and Bi does not cause changes in the chemical structure of Bi2WO6, proving that the analysis results of FT-IR are consistent with XRD

[0049] 2. Morphological Characterization of Photocatalysts

[0050] 2.1 SEM analysis

[0051] Figure 3 is the SEM image of the sample. Figure 3 (a, d) show the CBWO-5 samples prepared under static conditions. It can be observed that the composite samples prepared by static solvothermal treatment are tightly stacked into a flower shape with 2D nanosheets. Figure 3(b, e) are composite samples prepared by solvothermal reaction at a rotation speed of 60 rpm. It can be observed that with the introduction of the rotation method, the stacking mode of the CBWO-5 sample layers has changed, and an angle is formed between the 2D nanosheets. Figure 3 (c, f) are HCBWO-5 samples prepared at 90 rpm. Due to the increase in the rotation speed of the rotation method, the flower-shaped CBWO-5 stacked in a hollow nest structure microsphere is transformed into a 2D nanosheet randomly stacked and self-assembled. The larger cavity and the disordered staggered stacked thin nanosheets make the HCBWO-5 sample have a larger surface energy, which is beneficial to the mass transfer of the liquid phase system and can effectively improve the photocatalytic degradation efficiency.

[0052] 2.2 TEM analysis

[0053] like Figure 4 As shown in Figure 1, the microscopic morphology of HCBWO-5 prepared at 90 rpm can be observed by transmission electron microscopy (TEM). It can be clearly seen from the figure that the 2D nanosheets of the composite catalyst are disorderly stacked, and the light and dark changes in the middle indicate that HCBWO-5 has a large cavity, which is consistent with the SEM image.

[0054] 3. Elemental analysis of photocatalysts

[0055] X-ray photoelectron spectroscopy (XPS) was used to investigate the elemental composition and chemical state of the composites. Figure 5 (a) is the full spectrum of HCBWO-5 composite material, indicating that C / Bi / Bi2WO6 composite material is composed of four elements: C, Bi, W, and O. Figure 5 (b) shows the high-resolution XPS spectrum of Bi4f. The two strong peaks at 164.4 eV and 159.2 eV belong to Bi 4f, respectively. 5 / 2 and Bi 4f 7 / 2 The other two small peaks at 163eV and 158eV are attributed to metallic Bi. In addition, the high-resolution XPS spectrum of W 4f is shown in Figure 5 As shown in (c), the double peaks at 37.3 eV and 35.1 eV are attributed to W4f 5 / 2 and W 4f 7 / 2 , this is W 6+ Characteristics of oxidation states. Figure 5 (d) The high-resolution XPS spectrum of the C 1s signal is shown. The two peaks at 284.8 eV and 288.4 eV belong to the adventitious carbon species and CO3 in the composite material, respectively. 2- .

[0056] 4. Surface area test of photocatalyst

[0057] The specific surface area and pore characteristics of the prepared samples were analyzed by N2 adsorption-desorption. Figure 6As shown, both static and dynamic composite materials belong to type IV physical adsorption isotherms, and a hysteresis loop appears at P / P0=0.5-1.0, which belongs to type H3, indicating that there is a mesoporous structure in the sample, which is mainly due to the direct stacking pores of the sheets. Figure 6 It can be seen that all samples show a narrow pore size distribution, mainly distributed between 0-60nm. And it can be seen from the figure that HCBWO-5 prepared under 90rpm rotation speed has a larger specific surface area and pore size. It can be seen that rotation provides more active sites for the composite catalyst. It is consistent with the cavities formed by the above SEM and TEM.

[0058] 5. Band structure analysis

[0059] To evaluate the light absorption properties of the material, Figure 7 The UV-visible diffuse reflectance spectra of samples C / Bi / Bi2WO6 and pure Bi2WO6 are shown in Figure 2. It can be seen that all samples have absorption in the visible light region, and we can see that the absorption of HCBWO-5 samples is slightly red-shifted compared to that of CBWO-5 and Bi2WO6 samples, indicating that the light absorption range of the HCBWO-5 composite prepared by the rotation method is broadened, which may be one of the reasons for the improved photocatalytic performance. Figure 7 (b) It can be seen that the band gaps of HCBWO-5 and Bi2WO6 samples are 3.2eV and 3.15eV respectively. The band gap of the composite is wider than that of the pure substance, which is beneficial to the improvement of photocatalytic performance.

[0060] 6. Photoelectrochemical analysis of photocatalysts

[0061] In order to further understand the transfer and separation of photogenerated carriers, photocurrent response tests were carried out in a standard three-electrode system, such as Figure 8 As shown in the figure, a is the impedance diagram of the composite material. It can be seen from the figure that the Nyquist arc of the dynamic composite material is smaller than that of the static and pure CBWO, indicating that the charge transfer rate is faster, which shows that the charge transfer resistance on the surface of the composite is reduced, thereby improving the photocatalytic activity. As shown in b in the figure, the HCBWO-5 material shows good photocurrent responsiveness, has stable characteristics during on / off light irradiation, and has the highest photocurrent response, proving that it has the lowest electron-hole recombination efficiency.

[0062] 7. Activity test

[0063] 7.1 Performance Testing

[0064] Composite materials with different proportions were tested for degradation of NOR solution and CIP solution under visible light. Both NOR and CIP are fluoroquinolone antibiotics. Through photocatalytic degradation, quinolone antibiotics can be degraded into biodegradable compounds or small molecule inorganic substances. Fig. 9 As shown, the degradation of NOR and CIP using composite materials of different proportions shows that after 60 minutes of photoreaction, the photocatalytic degradation rate of NOR reaches 93.4%, and the photocatalytic degradation rate of CIP is 90.1%. The degradation of NOR using catalysts with different C / Bi loadings can verify that HCBWO-5 is the composite catalyst with the best C / Bi loading. And by comparing the dynamic and static, it can be seen that the dynamic effect is better, the degradation rate of photocatalytic degradation ((C-C0) / C0×100%) and kinetic analysis (-ln(C / C0)=k×t). C0 and C are the initial concentration and the concentration at each moment, respectively; t is the reaction time, and k is the pseudo-first-order reaction kinetic constant. Therefore, the slope of the -ln(C / C0) / t curve is the value of k, which can reflect the size of the degradation efficiency. By Fig. 9 (b) and Fig. 9 (d) It can be seen that the photocatalytic degradation of NOR and CIP by composite materials with different proportions conforms to the pseudo-first-order kinetic model. From the slope, it can be seen that the HCBWO-5 composite material formed by rotation has the fastest rate of degradation of NOR.

[0065] 7.2 Cycle Experiment

[0066] Fig.10 This is the regeneration cycle experiment result of HCBWO-5 composite material degrading NOR. In order to explore the stability of the composite catalyst, the photocatalytic activity of HCBWO-5 composite catalyst after repeated use was tested. After five cycles, the photocatalytic degradation effect of the catalyst did not decrease significantly. This shows that the catalyst has good cycle stability and can be reused.

[0067] 8. Free radical capture by photocatalysts

[0068] like Fig.11 As shown in the figure, using HCBWO-5 composite material as catalyst, by adding different scavengers to the photocatalytic liquid phase system, free radical capture experiments were carried out. The results show that the addition of EDTA-2Na and p-BQ has a significant inhibitory effect on the photocatalytic degradation effect of the composite material. + ), superoxide radicals (·O2 - ) is the main contributor to the degradation of NOR. The addition of IPA and AgNO3 did not significantly inhibit the photocatalytic degradation of the composite material, which indicates that hydroxyl radicals (·OH - ) and electron (e - ) is not the main reactant in photocatalytic degradation.

[0069] Photocatalytic mechanism of HCBWO-5 nanocomposites, such as Fig.12 As shown. It is well known that the utilization rate of light by a catalyst is the main factor affecting its photocatalytic activity, which is closely related to the separation of photogenerated electrons and holes and their diffusion from the internal region to the crystal surface. More importantly, the SPR effect of Bi can not only promote the separation of photogenerated carriers, but also enhance the absorption of visible light by the photocatalytic system, further improving the photocatalytic activity. In addition, the isolated C 2p state can introduce some hybrid energy levels on the Bi2WO6 valence band (VB), thereby increasing the visible light response range. Under visible light irradiation, both Bi2WO6 and Bi can be excited to produce electrons and holes. Electrons can be transferred from Bi to the CB of Bi2WO6 and then react with O2 to generate ·O2 - The remaining holes can react with H2O to generate OH. Finally, the generated active species (h + ,·O2 - ,·OH) to degrade pollutants.

[0070] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a C / Bi / Bi2WO6 heterojunction photocatalyst by a rotational crystallization method, characterized in that: The steps include: S1. Add Bi(NO3)3·5H2O to HNO3 solution and disperse by ultrasonic, then add ethylenediaminetetraacetic acid and stir vigorously to mix, adjust pH value with ammonia solution, and vacuum dry to obtain precursor EDTA-Bi; S2, dissolving Bi(NO3)3·5H2O in ethylene glycol, then adding a certain amount of EDTA-Bi powder to the above solution and stirring to obtain solution A; S3, dissolving Na2WO4·2H2O in ethylene glycol to obtain solution B; S4. Mix the A and B solutions in ethanol and stir, transfer to a reactor for rotational crystallization, wash and dry the obtained solid product, and then obtain a C / Bi / Bi2WO6 heterojunction photocatalyst.

2. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: In step S1, the ratio of Bi(NO3)3·5H2O, HNO3, and ethylenediaminetetraacetic acid is 10 mmol:30 mL:10 mmol.

3. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: In step S1, the concentration of the ammonia solution is 7-8 mol / L, and the pH value is 5-7; the vacuum drying is performed at 100° C. for 20 h.

4. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: In step S2, the ratio of Bi(NO3)3·5H2O to ethylene glycol is 7 mmol:10 mL; and the amount of EDTA-Bi powder added is 0.03-0.7 g.

5. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: In step S3, the ratio of Na2WO4·2H2O to ethylene glycol is 3.5 mmol:10 mL.

6. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: In step S4, the rotational crystallization speed is 60 rpm-150 rpm, the temperature is 120° C.-160° C., and the time is 24 hours.

7. The method for preparing C / Bi / Bi2WO6 heterojunction photocatalyst by rotational crystallization method according to claim 1, characterized in that: The mass percentage of Bi / bismuth tungstate is 1-20wt%; the drying process is vacuum drying at 80°C for 12h.

8. An application of a C / Bi / Bi2WO6 heterojunction photocatalyst prepared by the method for preparing a C / Bi / Bi2WO6 heterojunction photocatalyst by a rotational crystallization method according to any one of claims 1 to 7, characterized in that: After 60 minutes of photocatalysis, the C / Bi / Bi2WO6 heterojunction photocatalyst can degrade norfloxacin NOR by up to 93.4% and ciprofloxacin CIP by up to 90.1%.